Trends in surgical approaches and adnexal surgeries during hysterectomies for benign diseases between 2015–2021 - Zhu, Xuejiao; Xi, Hongli; Li, Zhifang; Wang, Xinping (Frontiers in Surgery, 2023)
Background Hysterectomy is a widely used surgical approach for benign gynecological conditions, although recently there have been differences in the surgical route selected in different regions. Aims To estimate recent temporal trends, this study collected data on surgical approaches and adnexal surgeries during hysterectomies for benign diseases at a single institute from 2015 to 2021. Materials and methods We retrospectively analyzed data from Xiangyang No.1 People's Hospital, Hubei University of Medicine in Xiangyang, China, and identified 1828 women who underwent hysterectomies for benign gynecologic conditions performed with or without bilateral salpingectomy (BS) or bilateral salpingo-oophorectomy (BSO) between January 2015 and December 2021. Results There was an upward trend in the performance of hysterectomy and hysterectomy with BS, and there was a difference in the trends of concomitant adnexal surgery between AH, TLH, and VH, especially in TLH with BS. Patient characteristics data demonstrated that the most frequent indication for hysterectomy was leiomyoma, especially in women aged 45 to 65. Compared to AH, TLH, and VH, the operative bleeding, duration of surgery, and length of hospital stays of patients undergoing TLH with BS and BSO was the lowest. The surgical approach to benign diseases has changed dramatically due to a growing proportion of patients choosing minimally invasive procedures. The laparoscopic approach is becoming popular due to its capacity to decrease intraoperative blood loss and reduce hospitalization. Conclusions We should put more emphasis on surgical training for the TLH approach and help gynecologic surgeons provide the proposed added benefit of BS to their patients.